Lithium iron phosphate positive electrode material and preparation method thereof, positive electrode plate and lithium ion battery
During the preparation process of lithium iron phosphate positive electrode material, the crystal growth and lithium ion diffusion channels of the material are adjusted by using the first and second dopants to solve the problems of poor cyclicity and poor rate performance of lithium iron phosphate positive electrode material, and a significantly improved cycle and rate performance is achieved.
Patent Information
- Application Number
- CN202510053547.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
AI Technical Summary
The existing lithium iron phosphate positive electrode materials have problems of poor cycleability and poor rate performance.
During the preparation of the lithium iron phosphate positive electrode material, a first dopant is first added to the precursor material to change the crystal growth direction and open the lithium ion diffusion channel, and then a second dopant is added to the lithium iron phosphate positive electrode material to hinder the disordered growth of the grains and maintain the shape of the lithium ion diffusion channel.
The circulation and rate performance of lithium iron phosphate positive electrode material has been significantly improved.
Smart Images

Figure CN119797312A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art
[0002] As a positive electrode material for batteries (such as batteries used in the field of new energy vehicles), lithium iron phosphate has attracted widespread attention due to its stable discharge voltage platform, high specific capacity, excellent stability, abundant raw materials, low cost and easy availability, and environmental friendliness. It has been rapidly industrialized and has become one of the most widely used positive electrode materials for lithium-ion batteries.
[0003] At present, the commonly used synthesis methods of lithium iron phosphate can be mainly divided into solid phase method and liquid phase method. Among them, the solid phase method mainly includes high temperature solid phase method, carbon thermal reduction method and microwave thermal method, etc.; the liquid phase method mainly includes hydrothermal / solvothermal method, sol-gel method, coprecipitation method, microemulsion drying method and spray pyrolysis method. Although the above methods can prepare lithium iron phosphate, the prepared lithium iron phosphate has the problems of poor cyclability and poor rate performance.
[0004] Therefore, it is urgent to propose a new method for preparing lithium iron phosphate positive electrode materials to solve the problems of poor cyclability and poor rate performance of existing lithium iron phosphate. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a lithium iron phosphate positive electrode material and its preparation method, a positive electrode plate and a lithium ion battery, aiming to solve the technical problems of poor cyclability and poor rate performance of the existing lithium iron phosphate.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps: dispersing an iron source, a phosphorus source, a lithium source, a first carbon source, a first dopant and a first solvent to obtain a first slurry; subjecting the first slurry to a drying and a sintering treatment once to obtain a precursor material; adding a second carbon source, a second dopant and a second solvent to the precursor material, and dispersing the resultant to obtain a second slurry; subjecting the second slurry to a secondary drying and a secondary sintering treatment to obtain a lithium iron phosphate positive electrode material; wherein the first dopant is selected from at least one of ammonium metavanadate, vanadium pentoxide, titanium dioxide, manganese trioxide and manganese carbonate, and the second dopant is selected from at least one of ammonium metavanadate, vanadium pentoxide, titanium dioxide, manganese trioxide and manganese carbonate, and the amount of the second dopant added is greater than the amount of the first dopant added.
[0007] In the technical solution of the embodiment of the present application, first, in the preparation process of the precursor material, by adding the first dopant, it can change the growth direction of the lithium iron phosphate crystals, open the lithium ion diffusion channel inside the material, and improve the conductivity; then in the preparation process of the lithium iron phosphate positive electrode material, by adding the second dopant, on the one hand, it can hinder the disordered growth of grains, avoid the production of large single crystal particles, thereby affecting the capacity of the material, and reduce the sample polarization and powder internal resistance, and at the same time it can form active sites on the surface of the material, which is conducive to increasing the lithium ion deintercalation sites; in addition, it can further maintain the shape of the lithium ion diffusion channel, and avoid the shrinkage of the lithium ion diffusion channel caused by secondary sintering; through the synergistic effect of the first dopant and the second dopant, the cycle performance and rate performance of the lithium iron phosphate positive electrode material are significantly improved.
[0008] In some embodiments, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is (0.94~0.99):1; the molar ratio of the lithium element in the lithium source to the iron element in the iron source is (1.01~1.1):1; the mass ratio of the first carbon source to the lithium iron phosphate positive electrode material is (6~8):100; the mass ratio of the second carbon source to the lithium iron phosphate positive electrode material is (2~4):100; the mass ratio of the first dopant to the lithium iron phosphate positive electrode material is (0.03~0.05):100; the mass ratio of the second dopant to the lithium iron phosphate positive electrode material is (0.06~0.1):100.
[0009] In this embodiment, by controlling the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source to be (0.94~0.99):1, the specific capacity, cycle life, electrical conductivity and structural stability of the precursor material can be improved; by controlling the molar ratio of the lithium element in the lithium source to the iron element in the iron source to be (1.01~1.1):1, the particles can be refined, the sintering and fusion between the particles can be alleviated, and it is helpful to improve the rate performance of the precursor material; by controlling the mass ratio of the first carbon source to the lithium iron phosphate positive electrode material to be (6~8):100, a uniform carbon coating layer can be formed on the surface of the lithium iron phosphate positive electrode material, forming vacancies, providing lithium ion diffusion channels, and increasing conductivity; by controlling the mass ratio of the second carbon source to the lithium iron phosphate positive electrode material to be (2~4):100, a network carbon coating structure can be further formed. structure, improve the conductivity of particles between particles, reduce the internal resistance of powder, and thus improve the rate performance of the material; by controlling the mass ratio of the first dopant to the lithium iron phosphate positive electrode material to (0.03~0.05):100, the lithium ion diffusion channel inside the material can be opened to improve the conductivity; by controlling the mass ratio of the second dopant to the lithium iron phosphate positive electrode material to (0.06~0.1):100, the disordered growth of grains can be hindered, and the production of large single crystal particles can be avoided, thereby affecting the capacity of the material, and reducing the sample polarization and the internal resistance of the powder. At the same time, it can form active sites on the surface of the material, which is beneficial to increase the deintercalation sites of lithium ions; in addition, it can further maintain the shape of the lithium ion diffusion channel, avoid the shrinkage of the lithium ion diffusion channel caused by the secondary sintering, and thus improve the cycle performance and rate performance of the material.
[0010] In some embodiments, the first carbon source includes a small molecule carbon source and a macromolecular carbon source, wherein the mass ratio of the small molecule carbon source to the macromolecular carbon source is (2~4):1; the small molecule carbon source is selected from at least one of glucose and sucrose; the macromolecular carbon source is selected from at least one of starch, PEG, PVC, and PVP.
[0011] In this embodiment, by controlling the mass ratio of the small molecule carbon source to the macromolecular carbon source to be (2-4):1, uniform coating of the carbon layer can be achieved with high compaction; at the same time, the sources of the small molecule carbon source and the macromolecular carbon source are wide and easy to obtain, which is conducive to industrial mass production.
[0012] In some embodiments, the iron source and the phosphorus source are independently selected from at least one of anhydrous ferric phosphate and dihydrate ferric phosphate; the lithium source is selected from at least one of lithium carbonate, lithium oxide, and lithium hydroxide monohydrate; the second carbon source is selected from at least one of pyrrole, alkanone, polystyrene, and polypyrrole; the first solvent is selected from at least one of water, methanol, ethanol, and glycerol; the second solvent is selected from at least one of water, methanol, ethanol, and glycerol.
[0013] In this embodiment, at least one of anhydrous iron phosphate and dihydrate iron phosphate is selected as the iron source, at least one of anhydrous iron phosphate and dihydrate iron phosphate is selected as the phosphorus source, at least one of lithium carbonate, lithium oxide, and lithium hydroxide monohydrate is selected as the lithium source, at least one of water, methanol, ethanol, and propylene glycol is selected as the first solvent, and at least one of water, methanol, ethanol, and propylene glycol is selected as the second solvent. The iron source, phosphorus source, lithium source, first solvent, and second solvent used are all low-priced and easily available materials, which are conducive to large-scale industrial production; at least one of pyrrole, alkanone, polystyrene, and polypyrrole is selected as the second carbon source. The selected second carbon source has a wide range of sources and is easy to obtain, which is conducive to large-scale industrial production. At the same time, by using the second carbon source for secondary carbon coating, the conductivity of particles between particles can be further improved, the internal resistance of the powder can be reduced, and the rate performance of the material can be improved.
[0014] In some embodiments, the solid content of the first slurry is 20~50%, and the particle size of the solid particles in the first slurry is 200~300nm; the solid content of the second slurry is 20~50%, and the particle size of the solid particles in the second slurry is 300~400nm; the primary sintering treatment specifically includes: sintering under an inert atmosphere, a sintering temperature of 700~850℃, and a sintering time of 5~19h; the secondary sintering treatment specifically includes: sintering under an inert atmosphere, a sintering temperature of 600~750℃, and a sintering time of 3~8h.
[0015] In this embodiment, the solid content of the first slurry and the second slurry is controlled to be 20-50%, so that the raw materials are fully dispersed, which is convenient for subsequent grinding; the particle size of the solid particles in the first slurry is controlled to be 200-300nm, and the particle size of the solid particles in the second slurry is controlled to be 300-400nm, which is convenient for subsequent sintering and makes the particles in the material uniform; in addition, the particle size of the solid particles in the first slurry is 200-300nm, which can obtain a precursor material with moderate specific surface area and internal resistance, which is beneficial to improving the rate performance and cycle performance of the precursor material; and the particle size of the solid particles in the second slurry is larger than that of the solid particles in the first slurry. This is because appropriately increasing the particle size of the solid particles in the second slurry is beneficial to the uniform doping of the second dopant, thereby And improve the performance of lithium iron phosphate positive electrode materials; by controlling the sintering temperature of the primary sintering treatment to 700~850℃ and the sintering time to 5~19h, the reaction is completed, a uniform carbon coating layer is obtained, vacancies are formed, lithium ion diffusion channels are provided, and conductivity is increased; by controlling the sintering temperature of the secondary sintering treatment to 600~750℃ and the sintering time to 3~8h, a network carbon coating structure is formed, the conductivity of particles between particles is improved, the internal resistance of the powder is reduced, and the rate performance of the material is improved; in addition, the sintering temperature and time of the primary sintering treatment are significantly higher than those of the secondary sintering treatment. This is because compared with the carbon coating of the secondary sintering, the primary sintering is mainly to improve the density and compaction of the material, and therefore, a higher sintering temperature and time are required.
[0016] In some embodiments, after the secondary sintering treatment, the sintering product obtained by the secondary sintering is further crushed to obtain large-particle materials and small-particle materials with different particle sizes, and the large-particle materials are mixed with the small-particle materials to obtain lithium iron phosphate positive electrode materials; wherein the mass ratio of the large-particle materials to the small-particle materials is (7~9): (1~3), and the particle size of the large-particle materials is 1.5~2μm, and the particle size of the small-particle materials is 0.5~0.9μm; and the mixing time is 4~6h.
[0017] In this embodiment, by controlling the mass ratio of large particle material to small particle material to be (7~9):(1~3), and the particle size of the large particle material is 1.5~2μm, the particle size of the small particle material is 0.5~0.9μm, and the mixing time is 4~6h, the compaction density of the lithium iron phosphate positive electrode material can be significantly improved.
[0018] In a second aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material prepared by any of the above preparation methods.
[0019] In the technical solution of the embodiment of the present application, the lithium iron phosphate positive electrode material has good cycle performance and rate performance.
[0020] In some embodiments, the compaction density of the lithium iron phosphate positive electrode material is 2.70-2.79 g / cm 3 .
[0021] In this embodiment, the compaction density of the lithium iron phosphate positive electrode material is controlled to be 2.70-2.79 g / cm 3 , which can further improve the electrochemical performance of lithium iron phosphate positive electrode materials.
[0022] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the above-mentioned lithium iron phosphate positive electrode material.
[0023] In this embodiment, the positive electrode plate includes the above-mentioned lithium iron phosphate positive electrode material, and thus has good cycle performance and rate performance.
[0024] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.
[0025] In this embodiment, the lithium-ion battery includes the above-mentioned positive electrode plate, and thus has good cycle performance and rate performance.
[0026] The beneficial effects of the present application are as follows: different from the prior art, the present application firstly adds a first dopant during the preparation of the precursor material, which can change the growth direction of the lithium iron phosphate crystals, open the lithium ion diffusion channel inside the material, and improve the conductivity; then, during the preparation of the lithium iron phosphate positive electrode material, by adding a second dopant, on the one hand, it can hinder the disordered growth of grains, avoid the production of large single crystal particles, thereby affecting the capacity of the material, and reduce the sample polarization and powder internal resistance, and at the same time, it can form active sites on the surface of the material, which is conducive to increasing the lithium ion deintercalation sites; in addition, it can further maintain the shape of the lithium ion diffusion channel, and avoid the shrinkage of the lithium ion diffusion channel caused by secondary sintering; through the synergistic effect of the first dopant and the second dopant, the cycle performance and rate performance of the lithium iron phosphate positive electrode material are significantly improved.
[0027] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is a flow chart of the preparation method of lithium iron phosphate positive electrode material for this application; Figure 2 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present application; Figure 3 This is the XRD diagram of the lithium iron phosphate positive electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0030] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0032] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0033] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0034] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0035] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0036] At present, the commonly used synthesis methods of lithium iron phosphate can be mainly divided into solid phase method and liquid phase method. Among them, the solid phase method mainly includes high temperature solid phase method, carbon thermal reduction method and microwave thermal method, etc.; the liquid phase method mainly includes hydrothermal / solvothermal method, sol-gel method, coprecipitation method, microemulsion drying method and spray pyrolysis method. However, the lithium iron phosphate prepared by the above synthesis methods has the problems of poor cyclability and poor rate performance.
[0037] In order to solve the technical problems of poor cyclability and poor rate performance of existing lithium iron phosphate, the present application provides a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery.
[0038] First, see Figure 1 The embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps: dispersing an iron source, a phosphorus source, a lithium source, a first carbon source, a first dopant and a first solvent to obtain a first slurry; subjecting the first slurry to a drying and a sintering treatment once to obtain a precursor material; adding a second carbon source, a second dopant and a second solvent to the precursor material, and dispersing the resultant to obtain a second slurry; subjecting the second slurry to a secondary drying and a secondary sintering treatment to obtain a lithium iron phosphate positive electrode material; wherein the first dopant is selected from at least one of ammonium metavanadate, vanadium pentoxide, titanium dioxide, manganese trioxide and manganese carbonate, and the second dopant is selected from at least one of ammonium metavanadate, vanadium pentoxide, titanium dioxide, manganese trioxide and manganese carbonate, and the amount of the second dopant added is greater than the amount of the first dopant added.
[0039] In the technical solution of the embodiment of the present application, first, in the preparation process of the precursor material, by adding a low content of the first dopant, it can change the growth direction of the lithium iron phosphate crystals, open the lithium ion diffusion channel inside the material, and improve the conductivity; then in the preparation process of the lithium iron phosphate positive electrode material, by adding a high content of the second dopant, on the one hand, it can hinder the disordered growth of grains, avoid the production of large single crystal particles, thereby affecting the capacity of the material, and reduce the sample polarization and powder internal resistance, and at the same time it can form active sites on the surface of the material, which is conducive to increasing the lithium ion deintercalation sites; in addition, it can further maintain the shape of the lithium ion diffusion channel, and avoid the shrinkage of the lithium ion diffusion channel caused by secondary sintering; through the synergistic effect of the first dopant and the second dopant, the cycle performance and rate performance of the lithium iron phosphate positive electrode material are significantly improved.
[0040] Furthermore, in some embodiments, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is (0.94~0.99):1; the molar ratio of the lithium element in the lithium source to the iron element in the iron source is (1.01~1.1):1; the mass ratio of the first carbon source to the lithium iron phosphate positive electrode material is (6~8):100; the mass ratio of the second carbon source to the lithium iron phosphate positive electrode material is (2~4):100; the mass ratio of the first dopant to the lithium iron phosphate positive electrode material is (0.03~0.05):100; the mass ratio of the second dopant to the lithium iron phosphate positive electrode material is (0.06~0.1):100.
[0041] In the technical solution of the embodiment of the present application, by controlling the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source to be (0.94~0.99):1, the specific capacity, cycle life, electrical conductivity and structural stability of the precursor material can be improved; if the iron-phosphorus ratio is too low, the specific capacity and cycle life of the precursor material will be reduced, and the crystal structure of lithium iron phosphate will be unstable, reducing the electrical conductivity and stability of the material; if the iron-phosphorus ratio is too high, iron phosphate impurities will be produced; by controlling the molar ratio of the lithium element in the lithium source to the iron element in the iron source to be (1.01~1.1):1, the particles can be refined, the sintering and fusion between the particles can be alleviated, and it is helpful to improve the rate performance of the precursor material; if the lithium-iron ratio is too low, the particles will increase, reducing the rate performance of the precursor material; if the lithium-iron ratio is too high, lithium phosphate impurities will be produced, thereby reducing the electrochemical performance of the lithium iron phosphate positive electrode material.
[0042] In the technical solution of the embodiment of the present application, by controlling the mass ratio of the first carbon source to the lithium iron phosphate positive electrode material to (6~8):100, a uniform carbon coating layer can be formed on the surface of the lithium iron phosphate positive electrode material to form vacancies, provide lithium ion diffusion channels, and increase conductivity; if the mass ratio of the first carbon source to the lithium iron phosphate positive electrode material is too low, the lithium iron phosphate positive electrode material cannot be completely coated, thereby reducing conductivity; if the mass ratio is too high, carbon residue will be caused, affecting the capacity of the lithium iron phosphate positive electrode material, thereby reducing the electrochemical performance of the lithium iron phosphate positive electrode material. By controlling the mass ratio of the second carbon source to the lithium iron phosphate positive electrode material to (2~4):100, a network carbon coating structure can be further formed, the conductivity of the particles between the particles can be improved, the internal resistance of the powder can be reduced, and the rate performance of the material can be improved; if the mass ratio of the second carbon source to the lithium iron phosphate positive electrode material is too low, the coating is incomplete, resulting in a decrease in conductivity and an increase in the internal resistance of the powder, thereby reducing the rate performance of the material; if the mass ratio is too high, carbon residue will be caused, affecting the capacity of the lithium iron phosphate positive electrode material and thus reducing the electrochemical performance of the lithium iron phosphate positive electrode material.
[0043] In the technical solution of the embodiment of the present application, by controlling the mass ratio of the first dopant to the lithium iron phosphate positive electrode material to (0.03~0.05):100, the lithium ion diffusion channel inside the material can be opened and the conductivity can be improved; if the mass ratio of the first dopant to the lithium iron phosphate positive electrode material is too low, the lithium ion diffusion channel inside the material cannot be completely opened, causing the material conductivity to decrease; if the mass ratio is too high, the excess first dopant cannot enter the lattice, hindering the lithium ion diffusion channel, reducing the conductivity, and thus reducing the electrochemical properties of the material. By controlling the mass ratio of the second dopant to the lithium iron phosphate cathode material to (0.06~0.1):100, the disordered growth of grains can be hindered, the generation of large single crystal particles can be avoided, thereby affecting the capacity of the material, and reducing the sample polarization and powder internal resistance. At the same time, it can form active sites on the surface of the material, which is beneficial to increase the lithium ion deintercalation sites; in addition, it can further maintain the shape of the lithium ion diffusion channel, avoid the shrinkage of the lithium ion diffusion channel caused by secondary sintering, and thus improve the cycle performance and rate performance of the material; if the mass ratio of the second dopant to the lithium iron phosphate cathode material is too low, it cannot hinder the particle growth, so that the sample polarization and powder internal resistance are increased, and the shape of the lithium ion diffusion channel cannot be maintained, which leads to a decrease in the cycle performance and rate performance of the material; if the mass ratio is too high, the particles are too refined, resulting in local aggregation of particles, while hindering the lithium ion diffusion channel, thereby reducing the cycle performance and rate performance of the material.
[0044] Specifically, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source can be 0.94:1, 0.95:1, 0.96:1, 0.97:1, 0.98:1, 0.99:1 or other ratios within the range; the molar ratio of the lithium element in the lithium source to the iron element in the iron source can be 1.01:1, 1.03:1, 1.05:1, 1.07:1, 1.09:1, 1.1:1 or other ratios within the range; the mass ratio of the first carbon source to the lithium iron phosphate positive electrode material can be 6:100, 6.5:100, 7:100, 7.5:100, 8:100 or other ratios within the range; The mass ratio of the second carbon source to the lithium iron phosphate positive electrode material can be 2100, 2.5:100, 3:100, 35:100, 4:100 or other ratios within this range; the mass ratio of the first dopant to the lithium iron phosphate positive electrode material can be 0.03:100, 0.035:100, 0.04:100, 0.045:100, 0.05:100 or other ratios within this range; the mass ratio of the second dopant to the lithium iron phosphate positive electrode material can be 0.06:100, 0.07:100, 0.08:100, 0.09:100, 0.1:100 or other ratios within this range.
[0045] Furthermore, in some embodiments, the first carbon source includes a small molecule carbon source and a macromolecule carbon source, wherein the mass ratio of the small molecule carbon source to the macromolecule carbon source is (2~4):1; the small molecule carbon source is selected from at least one of glucose and sucrose; and the macromolecule carbon source is selected from at least one of starch, PEG, PVC, and PVP.
[0046] In the technical solution of the embodiment of the present application, the mass ratio of the small molecule carbon source and the macromolecular carbon source is controlled to be (2~4):1, wherein the small molecule chain carbon source is carbonized first, and the "waste gas" generated during the carbonization process can disperse the material and inhibit the growth of particles during the formation of lithium iron phosphate. At the same time, part of the carbon produced by the small molecule chain carbon source is used as a reducing agent to reduce trivalent iron to divalent iron; the other part is used for carbon layer coating and distributed around the lithium iron phosphate in the form of amorphous carbon to increase the conductivity between particles; the macromolecular carbon source is subsequently carbonized, and most of the carbon chain A stable carbon skeleton is formed; through the synergistic effect of small molecule carbon sources and large molecule carbon sources, uniform coating of the carbon layer is achieved with high compaction; at the same time, the sources of small molecule carbon sources and large molecule carbon sources are wide and easy to obtain, which is conducive to industrial mass production; if the mass ratio of small molecule carbon sources to large molecule carbon sources is too low, the growth of particles in the process of lithium iron phosphate formation cannot be suppressed, and trivalent iron cannot be completely reduced to divalent iron, resulting in reduced conductivity; if the mass ratio is too high, the lithium iron phosphate particles are too fine, resulting in local aggregation, which significantly reduces the electrochemical properties of the material.
[0047] Specifically, the mass ratio of the small molecule carbon source to the macromolecular carbon source can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1 or other ratios within this range.
[0048] Further, in some embodiments, the iron source and the phosphorus source are independently selected from at least one of anhydrous ferric phosphate and dihydrate ferric phosphate; the lithium source is selected from at least one of lithium carbonate, lithium oxide, and lithium hydroxide monohydrate; and / or the second carbon source is selected from at least one of pyrrole, alkane, polystyrene, and polypyrrole; the first solvent is selected from at least one of water, methanol, ethanol, and glycerol; and the second solvent is selected from at least one of water, methanol, ethanol, and glycerol.
[0049] In the technical scheme of the embodiment of the present application, at least one of anhydrous iron phosphate and dihydrate iron phosphate is selected as the iron source, at least one of anhydrous iron phosphate and dihydrate iron phosphate is selected as the phosphorus source, at least one of lithium carbonate, lithium oxide, and lithium hydroxide monohydrate is selected as the lithium source, at least one of water, methanol, ethanol, and propylene glycol is selected as the first solvent, and at least one of water, methanol, ethanol, and propylene glycol is selected as the second solvent. The iron source, phosphorus source, lithium source, first solvent, and second solvent used are all low-priced and easily available materials, which are conducive to large-scale industrial production; at least one of pyrrole, alkanone, polystyrene, and polypyrrole is selected as the second carbon source. The selected second carbon source has a wide range of sources and is easy to obtain, which is conducive to large-scale industrial production. At the same time, by using the second carbon source for secondary carbon coating, the conductivity of particles between particles can be further improved, the internal resistance of the powder can be reduced, and the rate performance of the material can be improved.
[0050] Further, in some embodiments, the solid content of the first slurry is 20~50%, and the particle size of the solid particles in the first slurry is 200~300nm; the solid content of the second slurry is 20~50%, and the particle size of the solid particles in the second slurry is 300~400nm; the primary sintering treatment specifically includes: sintering in an inert atmosphere, the sintering temperature is 700~850℃, and the sintering time is 5~19h; the secondary sintering treatment specifically includes: sintering in an inert atmosphere, the sintering temperature is 600~750℃, and the sintering time is 3~8h.
[0051] In the technical solution of the embodiment of the present application, by controlling the solid content of the first slurry and the second slurry to be 20-50%, the raw materials are fully dispersed, which is convenient for subsequent grinding; if the solid content of the first slurry and the second slurry is too low, the prepared precursor material will be less, and multiple batching is required to obtain more precursor materials, which wastes manpower and material resources; if the solid content of the first slurry and the second slurry is too high, the raw materials cannot be fully dispersed, which is not convenient for subsequent grinding; by controlling the particle size of the solid particles in the first slurry to be 200-300nm and the solid particles in the second slurry to be 200-300nm, the raw materials are fully dispersed, which is convenient for subsequent grinding. The particle size of the body particles is 300~400nm, which is convenient for subsequent sintering to make the particles in the precursor material uniform; in addition, the particle size of the solid particles in the first slurry is 200~300nm, which can obtain a precursor material with moderate specific surface area and internal resistance, which is beneficial to improving the rate performance and cycle performance of the precursor material; and the particle size of the solid particles in the second slurry is larger than that of the solid particles in the first slurry. This is because appropriately increasing the particle size of the solid particles in the second slurry is beneficial to the uniform doping of the second dopant, thereby improving the performance of the lithium iron phosphate positive electrode material.
[0052] In the technical solution of the embodiment of the present application, the sintering temperature of the primary sintering treatment is controlled to be 700~850℃, and the sintering time is 5~19h, so that the reaction is complete, a uniform carbon coating layer is obtained, vacancies are formed, lithium ion diffusion channels are provided, and conductivity is increased; if the sintering temperature and time of the primary sintering treatment are too low, the reaction is incomplete, resulting in incomplete carbon coating, and the electrochemical properties of the material are reduced; if the sintering temperature and time of the primary sintering treatment are too high, the particles grow, and the electrochemical properties of the material are reduced; by controlling the sintering temperature of the secondary sintering treatment to be 600~750℃ and the sintering time to be 3~8h, a network carbon coating structure is formed, the conductivity of the particles between the particles is improved, and the powder is reduced. The internal resistance is reduced, thereby improving the rate performance of the material; if the sintering temperature and time of the secondary sintering treatment are too low, the reaction is incomplete, resulting in incomplete carbon coating and reducing the electrochemical properties of the material; if the sintering temperature and time of the secondary sintering treatment are too high, the particles will grow and the electrochemical properties of the material will decrease; in addition, the sintering temperature and time of the primary sintering treatment are significantly higher than those of the secondary sintering treatment. This is because compared with the carbon coating of the secondary sintering, the primary sintering is mainly to improve the density and compaction of the material, and therefore, a higher sintering temperature and time are required; if the primary sintering temperature and time are lower than the secondary sintering temperature and time, the compaction of the material will be reduced, causing the electrochemical properties of the material to decrease.
[0053] Specifically, the solid content of the first slurry can be, for example, 20%, 30%, 40%, 50% or other values within this range; the particle size of the solid particles in the first slurry can be, for example, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm or other values within this range; the solid content of the second slurry can be, for example, 20%, 30%, 40%, 50% or other values within this range; the particle size of the solid particles in the second slurry can be, for example, 300nm, 320nm, 340nm, 360nm , 380nm, 400nm or other values within this range; the sintering temperature in the primary sintering treatment may be, for example, 700°C, 750°C, 800°C, 850°C or other values within this range; the sintering time may be, for example, 5h, 10h, 15h, 19h or other values within this range; the sintering temperature in the secondary sintering treatment may be, for example, 600°C, 650°C, 700°C, 750°C or other values within this range; the sintering time may be, for example, 3h, 4h, 5h, 6h, 7h, 8h or other values within this range.
[0054] Furthermore, in some embodiments, after the secondary sintering treatment, the sintering product obtained by the secondary sintering is crushed to obtain large-particle materials and small-particle materials with different particle sizes, and the large-particle materials are mixed with the small-particle materials to obtain lithium iron phosphate positive electrode materials; wherein the mass ratio of the large-particle materials to the small-particle materials is (7~9): (1~3), and the particle size of the large-particle materials is 1.5~2μm, and the particle size of the small-particle materials is 0.5~0.9μm; and the mixing time is 4~6h.
[0055] In the technical solution of the embodiment of the present application, by controlling the mass ratio of large particle material to small particle material to be (7~9):(1~3), and the particle size of the large particle material is 1.5~2μm, the particle size of the small particle material is 0.5~0.9μm, and the mixing time is 4~6h, the compaction density of the lithium iron phosphate positive electrode material can be significantly improved; if the mass ratio of the large particle material to the small particle material is too low or too high, the compaction density of the lithium iron phosphate positive electrode material will be reduced.
[0056] In a second aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material prepared by any of the above preparation methods.
[0057] In the technical solution of the embodiment of the present application, the lithium iron phosphate positive electrode material has good cycle performance and rate performance.
[0058] Furthermore, in some embodiments, the compaction density of the lithium iron phosphate positive electrode material is 2.70-2.79 g / cm 3 .
[0059] In the technical solution of the embodiment of the present application, the compaction density of the lithium iron phosphate positive electrode material is controlled to be 2.70-2.79 g / cm 3 , which can further improve the electrochemical performance of lithium iron phosphate positive electrode materials.
[0060] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the above-mentioned lithium iron phosphate positive electrode material.
[0061] In the technical solution of the embodiment of the present application, the positive electrode plate contains the above-mentioned lithium iron phosphate positive electrode material, and thus has good cycle performance and rate performance.
[0062] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.
[0063] In the technical solution of the embodiment of the present application, the lithium-ion battery includes the above-mentioned positive electrode plate, and thus has good cycle performance and rate performance.
[0064] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0065] 1. Preparation method Example 1 A method for preparing a lithium iron phosphate positive electrode material comprises the following steps: S1. Preparation of raw materials: anhydrous iron phosphate is used as the iron source and the phosphorus source, lithium carbonate is used as the lithium source, glucose and PEG are used as the first carbon source, and the mass ratio of the two is 2:1, vanadium pentoxide is used as the first dopant, pyrrole is used as the second carbon source, and titanium dioxide is used as the second dopant, wherein the molar ratio of the iron element to the phosphorus element in the anhydrous iron phosphate is 0.94:1, the molar ratio of the lithium element in the lithium carbonate to the iron element in the anhydrous iron phosphate is 1.1:1, the mass ratio of the first carbon source to the prepared lithium iron phosphate is 6:100, and the mass ratio of the first dopant to the prepared lithium iron phosphate is 0.05:100; the mass ratio of the second carbon source to the prepared lithium iron phosphate is 4:100, and the mass ratio of the second dopant to the prepared lithium iron phosphate is 0.06:100; S2, weighing the raw materials in step S1 and adding them into water, controlling the solid content to 20%, then transferring them into a grinding system for grinding, controlling the output particle size range to be 300 nm, and obtaining a first slurry; spray drying the first slurry, and then placing the dry powder in a sintering furnace containing nitrogen, and sintering at a temperature of 700° C. for 19 hours, and obtaining a precursor material after cooling; S3, adding weighed pyrrole and titanium dioxide to the precursor material obtained in step S2, then adding water to the above mixture, controlling the solid content to 20%, and then transferring it to a grinding system for grinding, controlling the output particle size range to be 300nm, to obtain a second slurry; spray drying the second slurry, and then placing the dry powder in a sintering furnace containing nitrogen, and sintering at a temperature of 600°C for 8h, and pulverizing after cooling to obtain a large particle material with a particle size of 1.5-2μm and a small particle material with a particle size of 0.5-0.9μm; S4. The large particle material obtained in step S3 is mixed with the small particle material at a mass ratio of 9:1 for 4 hours to obtain a lithium iron phosphate positive electrode material.
[0066] Example 2 A method for preparing a lithium iron phosphate positive electrode material comprises the following steps: S1. Preparation of raw materials: anhydrous iron phosphate is used as the iron source and the phosphorus source, lithium oxide is used as the lithium source, sucrose and PVC are used as the first carbon source, and the mass ratio of the two is 3:1, manganese trioxide is used as the first dopant, alkane is used as the second carbon source, and vanadium pentoxide is used as the second dopant, wherein the molar ratio of iron element to phosphorus element in anhydrous iron phosphate is 0.97:1, the molar ratio of lithium element in lithium carbonate to iron element in anhydrous iron phosphate is 1.06:1, the mass ratio of the first carbon source to the prepared lithium iron phosphate is 7:100, and the mass ratio of the first dopant to the prepared lithium iron phosphate is 0.04:100; the mass ratio of the second carbon source to the prepared lithium iron phosphate is 3:100, and the mass ratio of the second dopant to the prepared lithium iron phosphate is 0.08:100; S2, weighing the raw materials in step S1 and adding them into water, controlling the solid content to 35%, then transferring them into a grinding system for grinding, controlling the output particle size range to 250 nm, and obtaining a first slurry; spray drying the first slurry, and then placing the dry powder in a sintering furnace containing nitrogen, and sintering at a temperature of 800° C. for 10 hours, and obtaining a precursor material after cooling; S3, adding weighed alkane and vanadium pentoxide to the precursor material obtained in step S2, then adding water to the above mixture, controlling the solid content to 35%, then transferring to a grinding system for grinding, controlling the output particle size range to 350nm, to obtain a second slurry; spray drying the second slurry, then placing the dry powder in a sintering furnace containing nitrogen, and sintering at a temperature of 700°C for 5h, and pulverizing after cooling to obtain a large particle material with a particle size of 1.5-2μm and a small particle material with a particle size of 0.5-0.9μm; S4. The large particle material obtained in step S3 is mixed with the small particle material at a mass ratio of 8:2 for 5 hours to obtain a lithium iron phosphate positive electrode material.
[0067] Example 3 A method for preparing a lithium iron phosphate positive electrode material comprises the following steps: S1. Preparation of raw materials: anhydrous iron phosphate is used as the iron source and the phosphorus source, lithium carbonate is used as the lithium source, glucose and PEG are used as the first carbon source, and the mass ratio of the two is 4:1, titanium dioxide is used as the first dopant, polystyrene is used as the second carbon source, and manganese carbonate is used as the second dopant, wherein the molar ratio of the iron element to the phosphorus element in the anhydrous iron phosphate is 0.99:1, the molar ratio of the lithium element in the lithium carbonate to the iron element in the anhydrous iron phosphate is 1.01:1, the mass ratio of the first carbon source to the prepared lithium iron phosphate is 8:100, and the mass ratio of the first dopant to the prepared lithium iron phosphate is 0.03:100; the mass ratio of the second carbon source to the prepared lithium iron phosphate is 2:100, and the mass ratio of the second dopant to the prepared lithium iron phosphate is 0.1:100; S2, weighing the raw materials in step S1 and adding them into water, controlling the solid content to be 50%, and then transferring them into a grinding system for grinding, controlling the output particle size range to be 200 nm, to obtain a first slurry; spray drying the first slurry, and then placing the dry powder in a sintering furnace containing nitrogen, and sintering at a temperature of 850° C. for 6 hours, and obtaining a precursor material after cooling; S3, adding weighed polystyrene and manganese carbonate to the precursor material obtained in step S2, then adding water to the above mixture, controlling the solid content to 50%, and then transferring to a grinding system for grinding, controlling the output particle size range to be 400nm, to obtain a second slurry; spray drying the second slurry, and then placing the dry powder in a sintering furnace containing nitrogen, and sintering at a temperature of 750°C for 4h, and pulverizing after cooling to obtain a large particle material with a particle size of 1.5-2μm and a small particle material with a particle size of 0.5-0.9μm; S4. The large particle material obtained in step S3 is mixed with the small particle material at a mass ratio of 7:3 for 4 hours to obtain a lithium iron phosphate positive electrode material.
[0068] Example 4 The preparation method of the lithium iron phosphate positive electrode material in this embodiment is basically the same as that in Example 1, except that the first dopant is a mixture of vanadium pentoxide and titanium dioxide, and the mass ratio of the two is 1:5; the second dopant is a mixture of titanium dioxide and manganese carbonate, and the mass ratio of the two is 1:6.
[0069] Example 5 The preparation method of the lithium iron phosphate positive electrode material in this embodiment is basically the same as that in Example 1, except that the first dopant is a mixture of vanadium pentoxide, titanium dioxide and manganese trioxide, and the mass ratio of the three is 1:4:2; the second dopant is a mixture of vanadium pentoxide, titanium dioxide and manganese carbonate, and the mass ratio of the three is 1:7:5.
[0070] Comparative Example 1 The preparation method of the lithium iron phosphate positive electrode material in this comparative example is basically the same as that in Example 1, except that the first dopant is not added.
[0071] Comparative Example 2 The preparation method of the lithium iron phosphate positive electrode material in this comparative example is basically the same as that in Example 1, except that the second dopant is not added.
[0072] Comparative Example 3 The preparation method of the lithium iron phosphate positive electrode material in this comparative example is basically the same as that in Example 1, except that the mass ratio of the first dopant to the prepared lithium iron phosphate is 0.06:100, and the mass ratio of the second dopant to the prepared lithium iron phosphate is 0.05:100.
[0073] Comparative Example 4 The preparation method of the lithium iron phosphate positive electrode material in this comparative example is basically the same as that in Example 1, except that the particle size of the solid particles in the first slurry is controlled to be 400 nm, and the particle size of the solid particles in the second slurry is controlled to be 200 nm.
[0074] Comparative Example 5 The preparation method of the lithium iron phosphate positive electrode material in this comparative example is basically the same as that in Example 1, except that in step S2, the sintering temperature is 600°C, and in step S3, the sintering temperature is 800°C.
[0075] Comparative Example 6 The preparation method of the lithium iron phosphate positive electrode material in this comparative example is basically the same as that in Example 1, except that the first carbon source is only glucose.
[0076] Comparative Example 7 The preparation method of the lithium iron phosphate positive electrode material in this comparative example is basically the same as that in Example 1, except that the first carbon source is only PEG.
[0077] Comparative Example 8 The preparation method of the lithium iron phosphate positive electrode material in this comparative example is basically the same as that in Example 1, except that in step S3, no pulverization treatment is performed after sintering, and the lithium iron phosphate positive electrode material is directly obtained.
[0078] 2. Test Method 1. SEM test The lithium iron phosphate cathode material prepared in Example 1 was subjected to SEM testing, and the results were as follows: Figure 2 shown.
[0079] 2. XRD test The lithium iron phosphate cathode material prepared in Example 1 was subjected to XRD test, and the results were as follows: Figure 3 shown.
[0080] 2. Lithium iron phosphate cathode material performance test The powder internal resistance (DC internal resistance test method), PD (compaction density test method) and BET (nitrogen adsorption method) of the lithium iron phosphate positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-8 were tested, and the results are shown in Table 1 below.
[0081] 3. Battery performance test The lithium iron phosphate positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-8 were processed and assembled into button batteries according to the button test method. The electrochemical properties of the batteries were tested. The results are shown in Table 2 below.
[0082] III. Analysis of test results of various embodiments and comparative examples from Figure 2 It can be seen that the lithium iron phosphate positive electrode material prepared in this application has a porous structure and the internal particles are relatively dense.
[0083] from Figure 3 It can be seen that the prepared lithium iron phosphate positive electrode material has fewer impurity peaks.
[0084] Table 1 Performance test results of lithium iron phosphate cathode materials
[0085] It can be seen from Table 1 that the lithium iron phosphate positive electrode materials prepared in Examples 1-5 have lower powder internal resistance and higher compaction density, and the compaction is slightly reduced after mixed doping (Examples 4 and 5), but the powder internal resistance is significantly reduced, and the BET is slightly larger, which is conducive to electrolyte infiltration and improves the capacity and electrochemical performance of the material. Combined with Comparative Examples 1-3, it can be seen that under the same conditions of single doping (Comparative Examples 1 and 2), the compaction is improved, but the powder internal resistance is significantly increased; the first doping amount is greater than the second doping amount (Comparative Example 3), the compaction is significantly reduced, and the powder internal resistance is significantly increased; it can be seen that single doping and the first doping amount greater than the second doping amount will increase the powder internal resistance, thereby reducing the electrochemical performance of the material. Combined with Comparative Example 4, it can be seen that the second slurry solid particle size is smaller than the first slurry particle size, which will improve compaction, but will cause uneven doping of the second dopant, increase the powder internal resistance, and thus reduce the electrochemical performance of the material. From comparisons 5-8, it can be seen that the primary sintering temperature is lower than the secondary sintering temperature (Comparative Example 5), the carbon source is not used in combination (Comparative Examples 6 and 7), and the powder is not pulverized (Comparative Example 8), all of which lead to poor particle density, large powder resistance, and large BET, thereby reducing the electrochemical properties of the material.
[0086] Table 2 Performance test results of lithium-ion batteries
[0087] As can be seen from Table 2, the lithium iron phosphate positive electrode materials prepared in Examples 1-5 have good electrochemical properties after being assembled into button batteries, and after mixed doping (Examples 4 and 5), the electrochemical performance of the battery is further improved. Single doping (Comparative Examples 1 and 2), the first doping amount is greater than the second doping amount (Comparative Example 3), the second slurry solid particle size is smaller than the first slurry particle size (Comparative Example 4), the primary sintering temperature is lower than the secondary sintering temperature (Comparative Example 5), the carbon source is not used in combination (Comparative Examples 6 and 7), and the non-crushing treatment (Comparative Example 8) will all lead to a decrease in the performance of the assembled battery. The results show that in this application, by performing two dopings during the preparation of the lithium iron phosphate positive electrode material and controlling other parameters, the performance of the lithium iron phosphate positive electrode material can be significantly improved, thereby improving the electrochemical performance of the battery assembled from the lithium iron phosphate positive electrode material.
[0088] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The steps include: The iron source, the phosphorus source, the lithium source, the first carbon source, the first dopant and the first solvent are dispersed to obtain a first slurry; The first slurry is subjected to a drying and a sintering process to obtain a precursor material; Adding a second carbon source, a second dopant and a second solvent to the precursor material, and performing a dispersion treatment to obtain a second slurry; The second slurry is subjected to secondary drying and secondary sintering to obtain a lithium iron phosphate positive electrode material; Among them, the first dopant is selected from at least one of ammonium metavanadate, vanadium pentoxide, titanium dioxide, manganese trioxide, and manganese carbonate, the second dopant is selected from at least one of ammonium metavanadate, vanadium pentoxide, titanium dioxide, manganese trioxide, and manganese carbonate, and the amount of the second dopant added is greater than the amount of the first dopant added.
2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is (0.94-0.99):1; and / or The molar ratio of the lithium element in the lithium source to the iron element in the iron source is (1.01-1.1):1; and / or The mass ratio of the first carbon source to the lithium iron phosphate positive electrode material is (6-8):100; and / or The mass ratio of the second carbon source to the lithium iron phosphate positive electrode material is (2-4):100; and / or The mass ratio of the first dopant to the lithium iron phosphate positive electrode material is (0.03-0.05):100; and / or The mass ratio of the second dopant to the lithium iron phosphate positive electrode material is (0.06-0.1):
100.
3. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The first carbon source comprises a small molecule carbon source and a macromolecular carbon source, wherein the mass ratio of the small molecule carbon source to the macromolecular carbon source is (2-4):1; and / or The small molecule carbon source is selected from at least one of glucose and sucrose; and / or The macromolecular carbon source is selected from at least one of starch, PEG, PVC and PVP.
4. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The iron source and phosphorus source are independently selected from at least one of anhydrous ferric phosphate and dihydrate ferric phosphate; and / or The lithium source is selected from at least one of lithium carbonate, lithium oxide, and lithium hydroxide monohydrate; and / or The second carbon source is selected from at least one of pyrrole, alkanone, polystyrene and polypyrrole; and / or The first solvent is selected from at least one of water, methanol, ethanol and glycerol; and / or The second solvent is selected from at least one of water, methanol, ethanol and glycerol.
5. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The solid content of the first slurry is 20-50%, and the particle size of the solid particles in the first slurry is 200-300 nm; The solid content of the second slurry is 20-50%, and the particle size of the solid particles in the second slurry is 300-400 nm; The primary sintering treatment specifically includes: sintering in an inert atmosphere, the sintering temperature is 700-850° C., and the sintering time is 5-19 hours; The secondary sintering process specifically includes: The sintering is carried out in an inert atmosphere, the sintering temperature is 600~750℃, and the sintering time is 3~8h.
6. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: After the secondary sintering treatment, the sintered product obtained by the secondary sintering is pulverized to obtain large particle materials and small particle materials with different particle sizes, and the large particle materials are mixed with the small particle materials to obtain a lithium iron phosphate positive electrode material; The mass ratio of the large particle material to the small particle material is (7-9): (1-3), the particle size of the large particle material is 1.5-2 μm, and the particle size of the small particle material is 0.5-0.9 μm; the mixing time is 4-6 hours.
7. A lithium iron phosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 7.
8. The lithium iron phosphate positive electrode material according to claim 7, characterized in that: The compaction density of the lithium iron phosphate positive electrode material is 2.70-2.79 g / cm 3 .
9. A positive electrode sheet, characterized in that: Including the lithium iron phosphate positive electrode material as described in claim 8.
10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Cited By
Double-layer carbon-coated lithium iron phosphate positive electrode material, preparation method thereof and battery
CN120637372A
Lithium iron phosphate material and preparation method thereof, positive pole piece, battery, energy storage device and electric equipment
CN121225558A
Iron phosphate material, lithium iron phosphate positive electrode material as well as preparation method and application of iron phosphate material and lithium iron phosphate positive electrode material
CN121672466A
Iron phosphate material, lithium iron phosphate positive electrode material as well as preparation method and application of iron phosphate material and lithium iron phosphate positive electrode material
CN121672467A